Towards to understanding the preliminary loss and absorption of nitrogen and phosphorus under different treatments in cotton drip- irrigation in northwest Xinjiang. - Honghong Ma (Public Library of Science (PLoS), 2021)
Drip irrigation under plastic mulch is widely used in Xinjiang, Northwest China. It can not only save water, but also reduce nutrient loss and improve fertilizer utilization. However, it is not clear whether the leaching occurs or not, what is the leaching amount? What is the relationship among fertilization, irrigation regimes, loss, cotton absorption, and cotton field under different fertilization and irrigation management under drip irrigation? Studying these issues not only provides reference for the formulation of fertilization and irrigation systems, but also is of great significance for reducing non-point source pollution. A long-term positioning experiment was conducted from 2009 to 2012 in Baotou Lake farm in Korla City, Xinjiang, with drip-irrigated cotton (Gossypium hirsutum L.) under different N fertilizer and irrigation amounts. The treatments were designed comprising Control (CK,0 N, 0 P, and 0 K with an irrigation of 480 mm) and the following three other treatments: (1) Conventional fertilize and irrigation (CON, 357 kg N hm-2, 90 kg P hm-2, 0 kg K hm-2, and irrigation of 480 mm); (2) Conventional fertilization and Optimizing irrigation (OPT, 357 kg N hm-2, 90 kg P hm-2, 62 kg K hm-2, and irrigation of 420 mm); and (3) Optimizing fertilization and irrigation (OPTN, 240 kg N hm-2, 65 kg P hm-2, 62 kg K hm-2, and irrigation of 420 mm). The results found that the leaching would occur in arid area under drip irrigation. The loss of total N, NH4+, P, N and P loss coefficient was higher under conventional fertilize and irrigation treatment while the loss of NO3- was higher under conventional fertilization and optimizing irrigation treatment. The correlations among N, P absorption by cotton, loss of NH4+ and total phosphorus were quadratic function. The total nitrogen loss and cumulative nitrogen application was lineally correlated. The loss of NO3- and cumulative nitrogen application was exponential. The nitrogen and phosphorus absorption by cotton under conventional fertilization and optimizing irrigation treatment was 24.53% and 35.86% higher than that in conventional fertilize and irrigation treatment, respectively. The cotton yield under conventional fertilization and optimizing irrigation treatment obtained higher than that in other three treatments. Therefore, the conventional fertilization and optimizing irrigation treatment was the optimal management of water and fertilizer in our study. These results demonstrate that reasonable water, nitrogen and phosphorus fertilize could not only effectively promote the absorption of nitrogen and phosphorus, but also reduce nitrogen and phosphorus losses under drip fertigation and plastic mulching.